Oscillatory stability and eigenvalue analysis of power system with microgrid - Yildirim, Burak; Gencoglu, Muhsin Tunay (Springer, 2018)
This paper shows the effects of microgrid (MG) integration, location, penetration and load levels on the power systems oscillating stability. The analysis work was carried out in the IEEE 14 bus test system which is widely used in stability studies. Stability studies were carried out with the help of eigenvalue analysis over linearized system models. HOPF bifurcation point detection was performed to show the effect of MGs on the system loadability margin. In the study results, it is seen that MGs affect system stability positively by increasing system loadability margin and has a damper effect on the critical modes of the system and the electromechanical local modes, but they reduce the damping amount of the electromechanical interarea modes.
Keywords: Eigenvalue analysis; Microgrid; HOPF bifurcation; Oscillatory stability